KOMPETENSI TEKNIS APARATUR PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN SANGGAU - Fransiska Febriana E42009017 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
The thesis entitled  "Competency of The Local Government Apparatus on Regional Development Planning Board of Sanggau Regency". The title chosen after observing the phenomena in the field of competence of the government apparatus that greatly influence the performance of the board / organization where the apparatus itself was assigned as measured by the level of knowledge, skills and behavior. Based on the phenomenon of the issues discussed in this thesis is on the technical competence through the educational and training to the government apparatus in accordance with Government Regulation No. 101 in 2000 on Educational and Training of Civil Servants. The formulation of this research problem is how the technical competence of the local government apparatus of Regional Development Planning Board (Bappeda) of Sanggau Regency. The research used a qualitative approach and descriptive research methods. The results of research that has been done is still finding the government apparatus who lack  of competencies, especially to implement the main tasks routinely. Therefore, to improve the competence of the apparatus then to the apparatus were participated in the educational and trainings in accordance with their field of work routinely. Keyword: Competence, Government Apparatus